The Effect Of The Application Of Government Accounting Standards On Employee Performance Through The Use Of Technology In Financial Management Agencies And Binjai City Regional Revenue - Satria Yudha Atmaja; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
The implementation of appropriate government accounting standards and the optimal use of technology are important factors in improving employee performance in the government sector. This study aims to find out and analyze the influence of the application of government accounting standards on employee performance mediated by the use of technology in the Binjai City Regional Financial and Revenue Management Agency. This study uses a causal associative quantitative approach. The sample used was the entire employee population totaling 186 people, with a saturated sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study show that the implementation of government accounting standards has a positive and significant effect on employee performance, with a T-statistical value of 4.197 > 1.96 and a P-value of 0.000 < 0.05, indicating that the increase in the implementation of government accounting standards can improve employee performance. In addition, the implementation of government accounting standards has a positive and significant effect on the use of technology, with a T-statistical value of 21.071 > 1.96 and a P-value of 0.000 < 0.05, which indicates that accounting standards encourage the use of technology in the implementation of tasks. The use of technology also has a positive and significant effect on employee performance, with a T-statistical value of 6.636 > 1.96 and a P-value of 0.000 < 0.05, which shows that increasing the use of technology can improve employee performance. In addition, the use of technology is able to mediate the influence between the application of government accounting standards on employee performance, shown by the T-statistical value of 6.166 > 1.96 and the P-value of 0.000 < 0.05. These results provide insight that the implementation of government accounting standards and the use of technology are effective strategies in improving employee performance at the Binjai City Regional Financial and Revenue Management Agency.